Fast track land reform and belonging: examining linkages between resettlement areas and communal areas in Zvimba District, Zimbabwe - Marewo, Malvern Kudakwashe (University of Cape Town, 2021)
This study examines whether beneficiaries of Zimbabwe's Fast Track Land Reform Programme (FTLRP) of 2000 in resettlement areas maintain linkages with communal areas of origin. Present studies about the FTLRP provide limited in-depth attention to the importance of understanding linkages with places of origin. The study sought to explore the extent to which beneficiaries of the FTLRP are connected to their communal areas of origin, as well as the implications of the ties. Analysis of linkages is through social relationships and labour exchanges between people in resettlement areas and communal areas. This was done through a conceptual framework of belonging, which helped explain the various attachments to places of origin. The study was guided by a qualitative research approach. A case study of Machiroli Farm, an A1 villagised settlement, and Zvimba communal areas (Ward 6), Mashonaland West, Zimbabwe was utilised. The study's main finding is that beneficiaries of the FTLRP in the A1 model on Machiroli Farm retain linkages with communal areas of origin; beneficiaries of the FTLRP acquired new land without discarding ties and relations with places of origin. Most respondents attached clear importance to maintaining linkages with places of origin. Some respondents did not maintain ties with places of origin because of conflicts and breakdowns in family ties, highlighting that belonging is not static. Evidence from this case study shows that maintenance of linkages assists with agricultural production and enhancing social relations. Another important finding is that belonging enforced the maintenance of relations through factors, such as familial relations, burial sites, clubs, ceremonies and labour exchanges with communal areas of origin. The study argues that belonging is an aspect that ties people together despite physical translocation. Thus, this study's contribution is that, within land reform debates, physical translocation does not break the bonds with, or ties to, places of origin. Belonging enables several functions, such as access to labour, mitigation of economic challenges and enhancement of social relations, as demonstrated by this case study. For scholarship, the study contributes to land reform debates by applying the concept of belonging, which has mostly been applied to border and migration studies policy. The framework of belonging within land reform reveals the importance of social, cultural, religious and economic effects in accessing labour and enhancing agricultural production in agrarian settings. The study draws the conclusion that beneficiaries of land reform desire to remain relevant to a host of political, economic, spiritual and social aspects anchored in places of origin. Therefore, resettlement does not break ties which people have with places of origin, people embrace the new without discarding the old relations.